Implementing an HIV Test and Treat Rapid Response Anti Retroviral Initiation Program in a Southern City with High HIV Incidence. (4th October 2017) - Nwanyanwu, Rita; Alcaide, Maria; Rodriguez, Allan; Soni, Manasi; Kolber, Michael; Wawezyniak, Andrew; Villamizar, Kira
Abstract: Background: Early initiation of antiretroviral (ART) after HIV diagnosis (Test and Treat Rapid Response, TTRR) is safe and acceptable, shortens the time to virologic suppression, reduces HIV associated morbidity and mortality, and can potentially decrease HIV transmission. Miami Dade County is first in the US for HIV incidence. As with other cities in the South, barriers to routine HIV care result in delays in engagement in care. The average time from HIV diagnosis at the Florida Department of Health (FDOH) STD clinic in Miami to ART initiation is 60 days. The University of Miami, in collaboration with the FDOH, implemented a pilot HIV TTRR program in 2016 whose aim is to speed up the process from initial HIV diagnosis to initiation of ART. This study describes enrolled patients' demographics and the time to ART initiation in the first year of implementation (March 2016–February 2017). Methods: When an individual is diagnosed with HIV at the FDOH STD clinic, a TTRR team consisting of a Disease Intervention Specialist, Patient Navigator, Case Manager, and HIV Provider, is activated. This team ensures that: 1) a visit with an HIV provider occurs within 48 hours; 2) ART is prescribed as soon as possible (1–7 days from diagnosis); and 3) provision of ART and appropriate follow up occurs at the initial visit. Demographics, laboratory results, and time to ART were recorded and summarized Results: In one year, 45 patients were enrolled (73% male, 27% female); 70% of male were MSM. A majority were foreign born (32% Cuba, 24% Haiti, 18% other Hispanic countries), and from ethnic minorities (53 % Hispanic, 30% African American). An HIV Provider evaluated 48% of the patients the same day of HIV diagnosis; 88% within 48 hours. The mean time to ART initiation was 6 days (37% same day, 69% <7 days). FTC/TAF/EVG/c was most frequently prescribed (91%). The mean viral load at initial presentation was 4.32 log10 (SD=1.1). The mean CD4 count was 463 cells/mm 3 (SD=263); 20% had less than 200 cells/mm 3 . All but one patient came to the next consecutive appointment. Conclusion: Implementation of a TTRR program is feasible in cities with recognized barriers to HIV care. TTRR programs should be essential components of HIV prevention efforts to control the spread of the HIV epidemic in the South. Funding from P30A1073961 and H97HA27433. Disclosures: All authors: No reported disclosures.